Strengthening The Character of Love for The Motherland Through Friday Nationalism Activities for Indonesian Children in Sentul, Malaysia - Putri Shela Oktaviani; Casnan; Oman Hadiana; Tio Heriyana; Tati Nurhayati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to provide knowledge and experience to students of Sanggar Bimbingan Sentul Malaysia about Strengthening the Character of Love for the Motherland through Friday Nationalism activities for Indonesian children in Sentul, Malaysia. The method of service activities uses focus group discussion (FGD) both internally as KKN-KI participants and of course the head of the foundation and teachers and their staff at the Sentul Guidance Center. The results of the activities of the program that have been carried out on Nationalism Friday are in the form of activities that can increase the love of the homeland and the spirit of nationalism as for these activities as follows; Introduction to Indonesian Religion, Introduction and training ceremonies, Playing traditional games to introducing national and regional compulsory songs. The existence of the Nationalism Friday program can increase their homeland's love for their own country.